Peningkatan Ekonomi Masyarakat Melalui Pengembangan Ekowisata Dermaga Perahu Di Desa Darussalam Kabupaten Bima - Kusumayadi, Firmansyah; Badar, Muhamad; Widakdo, Sugeng; Hidayanti, Mawar; Sakinah, Sakinah (Marsipature Hutanabe: Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service aims to empower the community in developing the boat dock area in Darussalam Village as a sustainable ecotourism area. The method used in this activity is direct outreach to the community and FGD (Focus Group Discussion). The results obtained show that the pier in Darussalam village has the potential to be developed into an ecotourism area based on its potential. This is also supported by the enthusiasm of the village community in managing the environment sustainably. There is a need for collaboration in developing ecotourism areas so that they can support improving the economy of the surrounding community. This service can indirectly increase community knowledge in managing natural resource potential, foster a mindset to collaborate to form a community that has the potential to increase community economic income, and create initiatives to form tourism awareness community groups as an effort to manage the sustainable environment.